Design and construction of a prototype of hydraulic generator for study and development of control strategies for electric power generation in underground mines (2013)
This paper presents the design and control of a hydraulic generator to produce energy in the underground mine EL UVO of the company Paz del Río S.A., taking advantage the water flows that are generated in the exploitation of iron ore. The generator is constituted of a Pelton wheel which receives water through a servo valve, and it is connected to a DC generator. It was developed a discrete controller by algebraic methods for controlling the servo valve with the aim of achieving a constant flow of water to the Pelton wheel, allowing a constant voltage generation.